THE ANALYSIS OF CONVERSATIONAL IMPLICATURE ON TVONE’S KABAR BANG ONE ANIMATED EDITORIAL CARTOONS - FLORENCIA, ERLISSA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Conversational Implicature, Mass Media, Animated Editorial Cartoon, Kabar Bang One.Journalistic product can be an option to communicate ideas and information, especially in criticizing issues. One of the features to share opinions and critics in journalistic product is editorial cartoons. Mostly, the intention in editorial cartoon is implicitly stated, therefore understanding the implied meaning is important. As a result, the cartoonist’s intention can be successfully delivered. In line with this, the writer conducted a study about conversational implicature in Kabar Bang One editorial cartoons, in which most of the utterances contain intended meanings. There are two research problems to be solved: (1) what are the types of conversational implicature found in Kabar Bang One animated editorial cartoons? and (2) what are the implied meanings of the conversational implicature found in Kabar Bang One animated editorial cartoons?The writer uses qualitative approach and document analysis in conducting the study. The data are utterances produced by the characters of Kabar Bang One animated editorial cartoons containing conversational implicature.This study reveals that both of the types of conversational implicature, that are generalized and particularized conversational implicature, are used by the characters in Kabar Bang One animated editorial cartoons. There are 70 utterances found which contain conversational implicature and they either obey or break the conversational maxim. Particularized conversational implicature dominates the results with 60 utterances, and 10 utterances belong to generalized conversational implicature. Particularized conversational implicature is the most frequently found type as context is required in understanding the intentions of the utterances. The context is mostly related to the social issues, politics, government policies, and law. The utterances and choice of words used in the editorial cartoons are aimed to express critics and publics’ view points.The writer suggests that English students who are interested in conducting a research in similar topic use other theories of implicature, such as Levinson’s (1983) and Horn’s (1989). They are also expected to analyze conversational implicature from other media, for instance comics, comic strips, newspaper headlines, presidential debates, or news interviews.